KONSEP DIRI WANITA MODEL FASHION SHOW DI PEKANBARU - Azhar, Stefy Adelia; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
A woman's life fashion show models synonymous with glamorous lifestyle, nightlife, and even sex. In order to meet the demands and lifestyle as a model, they often do things - negative things like, into prostitution "or being a mistress" This situation results in the emergence of a negative assessment of the community of women who worked as a model, even though it can not be in jendralisis. Departing from this condition researchers are interested to know how the woman's self concept models fashion show in Pekanbaru. This study aims to determine the dimensions of the internal and external dimensions of the model woman fashion show in Pekanbaru.This study uses qualitative research with phenomenological approach. Subjects consisted of five informants, who were selected through key informant named mas Raymond as the supreme mentor administrators Putri Indonesia Riau representatives, using techniques snowball technique. The study used data collection techniques of observation, interviews, and research documentation. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation. The research shows the internal dimensions of the model woman fashion show in Pekanbaru, self-identity that is a model woman, some of the informants came from poor families, life changed since the model works better established with the result being a mistress. Actors themselves that promiscuity and environmental influences make a drastic change. Self receiver is aware of the bad deeds, received negative comments from the public. Dimensions of the external female models fashion show in Pekanbaru. Physical self, perfect for the main requirement of a model. Moral ethical self, refusing to be grateful, not to close themselves to God. causing properties or characters that are easily affected by the surrounding environment . Self always perform imaging and lies. Self family , very close to the family , very supportive in the profession as a model . Social self is not arrogant if you meet someone who is known , friendly , nice , easy to make friends. But other things with friends in the profession (model ) , do have a sense of competition and jealousy.Keyword : Women Model, Fashion Show, and Self Consept